Richie ebook A father, his son, and the ultimate american tragedy. - Thompson, Thomas (Open Road Media, 2016)
The “powerful and moving” true story of a Long Island family torn apart by drugs, violence, and the unbridgeable divide between generations ( Kirkus Reviews ). George Diener, World War II veteran and traveling salesman, and his wife, Carol, had old-fashioned values and ordinary aspirations: a home, a family, the pleasure of watching their two sons grow up. But in February 1972, an unthinkable tragedy occurred in the basement of their Nassau County residence, shattering their hopes and dreams forever.   George and Carol doted on their shy eldest son, Richie. But at fifteen, the boy fell into a devastating downward spiral. He started smoking marijuana, shoplifting, and hanging out with drug dealers, and was soon arrested for assault and expelled from school. By the time his parents sought psychiatric counseling for their son, Richie was addicted to barbiturates and given to violent outbursts and threats. The boy George and Carol knew was long gone. Then, one winter evening, Richie came at his father with a steak knife and a suicidal cry of “Shoot!”   Edgar Award–winning author Thomas Thompson delivers a “scary, harrowing” account of a turbulent era in American history when the gulf between young and old, bohemian and conservative, felt wider and more dangerous than ever before ( The New York Times Book Review ). A tragedy of Shakespearean proportions, the devastating account of George and Carol Diener’s nightmare was adapted into The Death of Richie , a television movie starring Ben Gazzara, Eileen Brennan, and Robby Benson as Richie.